PENGARUH PRODUCT CATEGORY, PRICE PERCEPTION, DAN E-CUSTOMER EXPERIENCE TERHADAP REPURCHASE INTENTION PAKET PREMIUM - Ardian, Faril; Prabandari, Sri Palupi (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2022)
The purpose of this study is to identify the effects of product category, price perception, and e-customer experience on the intention of Spotify users to repurchase the application’s Premium Package. The effects to be proven are those of each independent variable on the dependent variable. This study is categorized as explanatory research as it explains the relationship between two or more symptoms or phenomena. Using judgment sampling method and non-probability sampling technique, 152 people were selected as the sample. They must be people living in Malang city with the minimum age of seventeen years who are or have the experience of subscribing Spotify’s Premium Package. The data analysis was performed using IBM’s Statistical Package for the Social Sciences (SPSS) version 26. This study finds that product category significantly influences repurchase intention, that e-customer experience significantly influences repurchase intention, and that price perception has no significant effect on repurchase intention.